Potential risk factors for caesarean scar pregnancy: a retrospective case–control study. Issue 2 (1st May 2021) - Gull, B; Klerelid, V; Jormeus, A; Strandell, A
Abstract: STUDY QUESTION: What are the important risk factors for having a caesarean scar pregnancy (CSP)? SUMMARY ANSWER: Independent risk factors were smoking in the first trimester, higher parity, and previous caesarean section (CS) before the index caesarean delivery. WHAT IS KNOWN ALREADY: A spectrum of risk factors for CSP has been suggested but not proven: parity, number of previous caesarean section, elective as opposed to emergency CS, IVF-pregnancy, breech presentation, previous gynaecological surgery as well as suture technique. STUDY DESIGN, SIZE, DURATION: This retrospective case-control study included 31 women with a CSP during the period 2003–2018 treated at a tertiary care centre for gynaecology and reproduction. A control cohort of 8300 women with a history of a CS and a subsequent delivery during the same time period was formed. PARTICIPANTS/MATERIALS, SETTING, METHODS: Variables describing demography, lifestyle factors, and reproductive and obstetric history were retrieved from medical records and the obstetric hospital database. Logistic regression analyses were applied to identify potential risk factors. MAIN RESULTS AND THE ROLE OF CHANCE: In a multivariable analysis, smoking in first trimester (adjusted odds ratio (OR) 3.03, 95% CI 1.01–9.07), higher parity (adjusted OR 1.30, 95% CI 1.03–1.64) and previous CS in addition to the preceding CS (adjusted OR 3.43, 95% CI 1.35–8.66) were independently predictive of a CSP. An elective CS at the index pregnancy was associated with an increased risk of CSP but did not remain significant in the multivariable analysis. LIMITATIONS, REASONS FOR CAUTION: CSP is a very rare phenomenon and several of the risk factor estimates are imprecise. Nevertheless, significant risk factors could be identified. Another limitation is the lack of electronically recorded details on suture techniques. WIDER IMPLICATIONS OF THE FINDINGS: The identified factors, namely higher parity and previous CS before the index caesarean section, are in accordance with previously suggested risk factors. Whether there is a true risk association between elective CS and future CSP needs to be investigated further. Smoking in the first trimester is a new finding, which has a plausible rationale. These factors should be recognised when counselling women after a caesarean delivery, particularly in a subsequent pregnancy with early complications. STUDY FUNDING/COMPETING INTEREST(S): This work was supported by a grant from the Swedish state under the agreement between the Swedish government and the county councils the ALF-agreement (ALFGBG-720291). None of the authors has any conflict of interest to declare.